A Golgi-Localized Sodium/Hydrogen Exchanger Positively Regulates Salt Tolerance by Maintaining Higher K+/Na+ Ratio in Soybean - Sun, Tianjie; Ma, Nan; Wang, Caiqing; Fan, Huifen; Wang, Mengxuan; Zhang, Jie; Cao, Jinfeng; Wang, Dongmei (Frontiers in Plant Science, 2021)
Salt stress caused by soil salinization, is one of the main factors that reduce soybean yield and quality. A large number of genes have been found to be involved in the regulation of salt tolerance. In this study, we characterized a soybean sodium/hydrogen exchanger gene GmNHX5 and revealed its functional mechanism involved in the salt tolerance process in soybean. GmNHX5 responded to salt stress at the transcription level in the salt stress-tolerant soybean plants, but not significantly changed in the salt-sensitive ones. GmNHX5 was located in the Golgi apparatus, and distributed in new leaves and vascular, and was induced by salt treatment. Overexpression of GmNHX5 improved the salt tolerance of hairy roots induced by soybean cotyledons, while the opposite was observed when GmNHX5 was knockout by CRISPR/Cas9. Soybean seedlings overexpressing GmNHX5 also showed an increased expression of GmSOS1, GmSKOR, and GmHKT1, higher K+/Na+ ratio, and higher viability when exposed to salt stress. Our findings provide an effective candidate gene for the cultivation of salt-tolerant germplasm resources and new clues for further understanding of the salt-tolerance mechanism in plants.